Three-dimensional kinematics of the cervical spine using an electromagnetic tracking device. Differences between healthy subjects and subjects with non-specific neck pain and the effect of age - Lemmers, G.P.G.; Heijmans, M.W.M.; Scafoglieri, A.; Buyl, R.; Staal, J.B.; Schmitt, M.A.; Cattrysse, E. (Clinical biomechanics (Bristol), 2018)
A cross-sectional observational study of three-dimensional cervical kinematics in 35 non-specific neck pain patients and 100 asymptomatic controls. To compare qualitative and quantitative aspects of cervical kinematics between healthy subjects and subjects with non-specific neck pain and to determine the effect of age on cervical kinematics in healthy subjects. Three-dimensional kinematics of active lateral bending and flexion-extension of 35 patients and 100 controls were registered by means of an electromagnetic tracking system. The means of several kinematic parameters were compared using t-tests. In addition, we assessed the age-dependency of the three-dimensional kinematic parameters by stratifying the 100 control subjects in 6 age categories. Comparison of the patient group with the control group reveals no statistically significant differences in qualitative and quantitative parameters. Analysis of the effect of age showed that the range of motion decreases significantly (p < 0.01) with increasing age. In lateral bending, the ratio between axial rotation and lateral bending increases significantly (p < 0.01) among older subjects. Differences in acceleration, jerk and polynomial fit are seen between the age categories, but are not significant. This study demonstrates no significant differences in kinematic parameters between healthy subjects and subjects with non-specific neck pain. Healthy subjects in higher age categories demonstrate higher ratios of coupled movements and lower ranges of motion. Future research should focus on classifying patients with non-specific neck pain in order to gain a better insight on possible subgroup specific differences in kinematics. More studies on this subject are warranted. Level of evidence: 4. •No differences in kinematics between patients with nonspecific neck pain and controls•Age-related differences for range of motion, ratio and qualitative kinematics•Future research should focus on classifying patients with non-specific neck pain.